Advanced stories for reproduction 1 - Hill, L. A. (Oxford Univ. Press, 1965)
Training students to reproduce material they have listened to or read, this book contains short anecdotes, followed by a set of comprehension questions on the passage. It also includes a complete wordlist at the back.